Stunting Di Gampong Lae Motong Kecamatan Penanggalan Kota Subulussalam - Nurhidayati, Rina (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2025)
Stunting, or impaired growth and development in children, has become a global issue, including in Indonesia. This is concerning because children are the foundation of the future generation, and poor child development can negatively affect the nation's future. In Aceh, the prevalence of stunting remains high compared to other provinces, affecting both urban and rural areas. In the village (Gampong) of Lae Motong, for example, 12 out of 135 children under five years old (approximately 9%) are stunted. This study aims to explore the reasons behind the high rate of stunting in Gampong Lae Motong and to examine the role of the local government in addressing this issue. The researcher used a qualitative descriptive method by collecting data through observation, interviews, and document analysis. The findings reveal several causes of stunting in the village, including: a) lack of nutritious food intake, b) infectious diseases, c) parenting patterns, d) poor sanitation and limited access to clean water, e) economic challenges, and f) low educational levels. The role of the village government has so far been limited to providing supplementary food and offering community education, which the researcher considers insufficient. Based on these findings, it is recommended that the government and relevant stakeholders work together to improve the community’s economy, raise awareness about child nutrition, and develop health-related infrastructure, particularly access to clean water.